Relationship between fragmented QRS complexes in leads V4-V6 and left ventricular apical thrombus formation in patients presenting with first acute anterior myocardial infarction - Erkan Baysal; Cengiz Burak; Barış Yaylak; Bernas Altıntaş; Önder Öztürk; Hacı Çiftçi; Rojhat Altındağ; Serdar Söner (KARE Publishing, 2017)
Objective: The present study was an investigation of the relationship between fragmented QRS (fQRS) and left ventricular apical thrombus (LVAT) in patients presenting with first acute anterior myocardial infarction (MI). Methods: Consecutive 148 patients (mean age: 60.1+-10.1 years; male: 75.6%) with first acute anterior MI who underwent primary percutaneous coronary intervention (PCI) were included. Study population was divided into 2 groups based on presence of LVAT. fQRS was defined as presence of various RSR' patterns, which included additional R wave or notching of R wave or S wave, and presence of more than 1 R in 2 contiguous leads corresponding to major coronary artery territory on 12-lead electrocardiogram. Patients with bundle branch block were excluded from the study. Results: Of these, 32 (21.6%) had LVAT. Patients with LVAT had higher prevalence of fQRS (53.1% vs. 22.4%; p<0.001) and lower rate of successful PCI (75% vs. 94%; p=0.002) compared with patients without LVAT. More patients in LVAT group had left ventricular ejection fraction of <30% (87.5% vs 65.5%; p=0.010). Groups were similar with respect to other baseline characteristics (p>0.05 for all). Presence of fQRS was independent predictor of LVAT (odds ratio [OR], 2.795; 95% confidence interval [CI], 1.058-7.396) in multivariable logistic regression analysis. Conclusion: Presence of fQRS in leads V4-V6 is independently associated with LVAT in patients presenting with first acute anterior MI.